Alternative proof of the Fermat’s last Theorem - Wong, Nelson VK (Eximia, 2023)
The Fermat's last theorem, has attracted the attention of mathematicians for more than three centuries. Many clever methods have been devised to attack the problem, and many beautiful theories have been created with the aim of proving the theorem. Yet, despite all the attempts, the question remains unanswered. The first successful proof was released in 1994 by Andrew Wiles and formally published in 1995 with over 100 pages. But I don’t think it would not be the original un-written proof by Fermat, the proof should be much simple. Maybe people were sidetracked to other directions. Thing should go directly to the question without changing any of the conditions nor adding addition conditions. The paper introduces a re-defining the problem and based on the Fermat equation for n=2 as the foundation of the proof, follow by induction approach and finish the proof.